Blackboxing leadership: Methodological practices leading to manager-centrism. (February 2023) - Larsson, Magnus; Alvehus, Johan
The scholarly literature on leadership has long been characterized by leader-centrism, in the sense of a focus on individual leaders, their characteristics and actions. This tendency has been strongly criticized, not least by scholars with a critical perspective. However, we still see a strong emphasis on leaders and managers in empirical studies of leadership. In this article, we suggest that this tendency is at least in part a consequence of common methodological blackboxing practices within leadership studies. We identify two such blackboxing practices: delegation, where identification of the core phenomenon is left to informants, and proxying, when more easily defined phenomena are taken to stand for leadership. We suggest that a consequence of such practices is an unintended focus on managers, and attempts to avoid leader-centrism that rely on these blackboxing practices therefore paradoxically might result in manager-centrism.